Introduction to the Environment and Workflow through the Implementation of the FIFO Program and Modernization in Wholesale Store Operations at PT. Indomarco Prismata Di Indogrosir Kemayoran Branch - Phymendyta Aldaning Azaria; Patricia Christie Watulangkou (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
To meet the needs of the community in this segment, PT. Indomarco Prismatama formed a company, namely PT. Inti Cakrawala Citra, also known as Indogrosir. PT. Inti Cakrawala Citra is a company that does business in the wholesale or wholesale sector and has spread throughout Indonesia. This company has experience since 1993 with the vision of “Being a national asset in a modern distribution network that excels in global competition” and has a mission of “generating and developing entrepreneurs in the retail sector”. Indogrosir continues to grow by maximizing the needs of the community, especially small traders with the motto "trusted business partner". Indogrosir stores can operate properly, of course supported by employees who have the main skills related to managing and supervising store operations and the ability to provide services to consumers. The control of employees inside the store is very important because it is related to the supervision and management of merchandise so that they are always available to consumers, especially with the Modernization program to facilitate product arrangement and search by consumers and Fifo which is applied to smooth store operations, especially in product turnover in stores. to consumers. Internship program at a grocery store starting from August 23, 2021 – February 23, 2022 This will train students to master competencies in wholesale stores. This internship program is designed based on the main basic needs of Indogrosir in-store learning, which all begin with an introduction to in-store operations. This program will also later provide support for an appropriate and sustainable learning system for students through internships at the Indogrosir Operations department..